Revision of Australian jumping spider genus Servaea Simon 1887 (Aranaea: Salticidae) including use of DNA sequence data and predicted distributions - Richardson, Barry J.; Gunter, Nicole L. (Zootaxa, 2012)
The genus Servaea Simon 1887 is revised and redefined. Descriptions and identification keys are provided to the following sixspecies, of which three are described as new: Servaea incana (Karsch 1878), Servaea narraweena n. sp., Servaea melaina n.sp., Servaea spinibarbis Simon 1909, Servaea villosa (Keyserling 1881) and Servaea zabkai n. sp. The type species of thegenus, Servaea vestita (L. Koch 1879), is proposed here to be a junior synonym of Servaea incana. In addition to the diagnosesand descriptions, distributional and nucleotide sequence information are provided. DNA sequence data for the segment of COIused in other salticid studies was obtained for the five species for which suitable material was available. Intraspecific variationin S. villosa and S. incana were studied in more detail. Within-species divergence was S. melaina and S spinibarbis, had adjacent predicted distributions, one coastal on sandy soils and one inland on other soil types.